Does financial development moderate the impact of climate mitigation innovation on CO2 emissions? Evidence from emerging economics - Raphael W. Apeaning; Musah Labaran (Innovation and Green Development)
Using a panel dataset of six emerging economies from 1990 to 2021, the study analyzed the moderating influence of financial institutions and markets on the deployment of Climate Mitigation Innovation (CMI) and its impact on carbon emissions. Our results from BRIICS countries (i.e. Brazil, Russia, India, Indonesia, China, and South Africa) reveal that sound financial systems significantly amplify the efficacy of CMI in lowering CO2 intensity. This research contributes to the existing body of knowledge by elucidating the conditional dynamics between financial development, technological innovation, and emission outcomes. Insights from the study underscore that emerging countries should strengthen their financial sectors to effectively leverage CMI for substantial emission reductions. Ultimately, insights gleaned from this study contribute to the growing literature on green innovation and green finance and serve as a basis for policymakers to craft strategies that enhance sound financial environment while promoting green technological innovations.